Pengaruh Pemasaran Melalui Media Sosial Instagram Terhadap Keputusan Pembelian: Survey Terhadap Konsumen @Drizzy_Apparel - Salsabila Fitri Shabrina; Isniyunisyafna Diah Delima; Alamsyah Alamsyah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Information and communication technology has become an important part of society's life without boundaries, technological advances that are currently being used by business people, namely marketing through social media, in this study the AIDA model theory and quantitative approach methods are used and the object of this research is consumers. Drizzy Apparel, and taking a sample of 100 respondents. The results of this study state that marketing through social media has a significant and positive effect on purchasing decisions made by Drizzy Apparel because it has a total tcount value of 10.848 and a ttable value of 1.661 so that Tcount > Ttable (10.848 > 1.661), so that means social media marketing positive and significant effect.